The Effect of Project Based Learning Model (PjBL) Assisted by KOKAMI Media on Motivation and Learning Outcomes on Chemical Equilibrium Material - Tampubolon, Cindy Claudin; Riris, Ida Duma; Nainggolan, Bajoka; Syafriani, Dewi; Ginting, Elfrida (Pascasarjana, Mataram University, 2025)
This study aims to determine the learning of the Project Based Learning (PjBL) Model assisted by KOKAMI media (Kotak dan Kartu Misteri) on learning outcomes, learning motivation, and the significance between learning outcomes and motivation in chemical equilibrium materials at SMA Negeri 17 Medan. The sample population of all students in grade XI and as a random sample was taken from two classes, namely class XI B as an experimental class and XI C as a control class. The initial learning was carried out in the same pre-test, then learning was carried out for the control class (using the conventional model without KOKAMI media) while the experimental class (using the PjBL model with the help of KOKAMI media). The results data were analyzed using normality, homogeneity, and linearity tests. The hypothesis was tested by simple linear regression, independent t-test, and correlation test. The average pre-test score of the experimental class was 34,00 8,17 the control class was 33,14 6,57 post-test (89.71 3.60 ; 79.57 6.36), with a higher N-Gain value (0.84 0.065 ; 0.69 0.016 ). The results of the simple linear regression test showed a significance value of 0.000 ≤ (α = 0.005) with an average learning motivation of 87.25 (high category), so that Ha was accepted. The t-test shows the value of sig. 0.000 ≤ (α = 0.005), and the third hypothesis test showed sig. 0.001 ≤ (α = 0.005), indicating a significant relationship between learning outcomes and learning motivation